Bayesian Estimators of the parameter and Reliability Function of Inverse Rayleigh Distribution" A comparison study " - Abod, Masooma Ali; Gorgee, Hazim Mansoor (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this paper, Bayesian estimator for the parameter and reliability function of inverse Rayleigh distribution (IRD) were obtained Under three types of loss function, namely, square error loss function (SELF), Modified Square error loss function (MSELF) and Precautionary loss function (PLF),taking into consideration the informative and non- informative prior. The performance of such estimators was assessed on the basis of mean square error (MSE) criterion by performing a Monte Carlo simulation technique.